(untitled) (Canadian Medical Education Journal, 2022)
Background: Research is an integral part of surgical training and a mandated competency by national accreditation bodies. Most residents engage in research, but the conversion of this research into peer-reviewed publications is unknown. The objectives of this study were to assess the conversion rate of resident research into published manuscripts and determine what variables predict publication. Methods: Through a retrospective design, 99 resident research abstracts were identified from the Surgery Research Day at the University of Saskatchewan 2008-2018. Publication status was verified using Google Scholar and PubMed. Variables associated with resident-specific, mentor-specific, and project-specific variables were assessed for their role in predicting publication. Results: Fifty-two (53%) of the 99 abstracts were published in a peer-reviewed journal, and 43 (43%) were presented at a national conference. Logistic regression analysis revealed multidisciplinary research (OR 4.46, CI 1.8-11.4, p = 0.002), projects involving multiple resident researchers (OR 2.56, CI 1.02-6.43, p = 0.045), and faculty supervisor having > 25 publications (OR 2.46, CI 1.03-5.88, p = 0.042) as significant predictors of publication. Conclusions: Our study identifies 3 variables related to collaboration and mentorship that can serve as potential starting points to increase research productivity amongst medical trainees.